Flight test of a laminar flow swept wing with boundary layer control by suction - Landeryou, R. R.; Trayford, R. S. (Cranfield University, 1964)
Flight tests have been performed on a laminar flow swept wing with 43 degree sweepback having slitted surfaces. The aim of the experiment was to achieve complete laminar flow unit Reynolds number of 1.5 x 10(6)ft (-1) which corresponds to 10.5 x 10(6) based on the wing geometric chord. The test wing and installation is described and the progress of the tests so far performed is reported. The most significant result to date has been the establishment of a critical Reynolds number above which turbulent disturbances will propagate along the attachment line when conditions are such that the momentum thickness Reynolds number of laminar boundary layer flowing along the attachment line would exceed 88. This has so far prevented the achievement of laminar flow at a unit Reynolds number of 1.5 x 10(6)ft(-1). The critical Reynolds number of 88 corresponds to a Reynolds number based on leading edge radius of 1.15 x 10(5) or 8.37 x 10(6) based on the stramwise chord. The progress of attemps to prevent the spread of these disturbances is reported.